2004
DOI: 10.1227/01.neu.0000143373.74160.f2
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas Invading the Superior Sagittal Sinus: Surgical Experience in 108 Cases

Abstract: On the basis of our results, we conclude that if the sinus is partially invaded, it can be opened to obtain as complete a resection as possible and to attempt to preserve the patency of the sinus. If the sinus is obstructed, the portion of the sinus involved can be resected completely. In both situations, extreme care is vital to preservation of cortical veins, which may offer important collateral drainage. With our approach, good results are achieved and it is not necessary to reconstruct the sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 30 publications
5
105
2
2
Order By: Relevance
“…Although historically this practice was generally accepted and performed routinely, studies on parasagittal meningiomas involving the superior sagittal sinus have shown that resection of occluded portions can interrupt collateral venous drainage, which may lead to venous hypertension and its sequelae in some patients if venous flow is not restored. 4,13,15,21,43 While few studies have documented outcomes after resection of occluded portions of the transverse sinus, similar morbidity would likely occur if collateral flow is disrupted, affecting veins corresponding to the inferior cerebral veins of Labbé. Therefore, venous reconstruction may be useful to restore outflow of the compensatory collateral channels that may have developed as the intraluminal tumor obstructed venous drainage.…”
Section: Surgical Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Although historically this practice was generally accepted and performed routinely, studies on parasagittal meningiomas involving the superior sagittal sinus have shown that resection of occluded portions can interrupt collateral venous drainage, which may lead to venous hypertension and its sequelae in some patients if venous flow is not restored. 4,13,15,21,43 While few studies have documented outcomes after resection of occluded portions of the transverse sinus, similar morbidity would likely occur if collateral flow is disrupted, affecting veins corresponding to the inferior cerebral veins of Labbé. Therefore, venous reconstruction may be useful to restore outflow of the compensatory collateral channels that may have developed as the intraluminal tumor obstructed venous drainage.…”
Section: Surgical Planningmentioning
confidence: 99%
“…33 Other recent retrospective series with a 10-year follow-up or less documented much lower rates of recurrence. 5,13,43 In a review of the literature on meningiomas involving the superior sagittal sinus, Tomasello et al 49 stratified study populations by treatment strategy from conservative to most radical: total resection in the setting of complete sinus obstruction or when the sinus was "only marginally involved"; resection of an intrasinus tumor requiring patching of the sinus but not venous reconstruction; and radical resection of a tumor with massive sinus involvement requiring bypass techniques to restore sinus outflow. These authors found that the recurrence rate was 6%-29% when a conservative strategy was adopted; 14%-19% when an intrasinus tumor was resected, requiring sinus repair but not reconstruction; and 4% when sinus outflow was restored after tumor resection.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…Series of superior sagittal sinus meningiomas emphasize some complications in the peroperative period [3,4,7]. These complications include postoperative hematoma, venous air embolism, subgaleal fluid collection, new onset of seizures, deep venous thrombosis, brain edema and transient or permanent neurological worsening in the immediate postoperative period [2,3,4,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas may result in hyperostosis of adjacent bone and frequently show calcification and the classic histological feature of psammoma bodies [2][3][4][5]. Parasagittal meningiomas make up of 20% of all meningiomas [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation